Women’s Suffrage: A Cinematic Study - Suzanne Bouclin (Revue LISA)
Cinema reflects actualities about law but it also shapes other possibilities for law. These assumptions guide my case study of the women’s suffrage movement in the United States and the conflicting conceptualizations of women’s equality in which that movement was embedded. Drawing on methods from feminist jurisprudence, intersectionality namely, I locate Katja von Garnier’s film Iron Jawed Angels (2004) in its historical, legal and discursive contexts to suggest how it constitutes meaning about the solidarities and divergences within the American women’s movement at the turn of the 20th century. I do so through a close reading of three key moments in the film’s narrative which suggest how women’s participation or lack thereof, in formal institutions, remains today, an indicator of aspirational and actualized gender equality.